Essential Self-Adjointness of Anticommutative Operators - Toshimitsu Takaesu (Journal of Mathematics)
The self-adjoint extensions of symmetric operators satisfying anticommutation relations are considered. It is proven that an anticommutative type of the Glimm-Jaffe-Nelson commutator theorem follows. Its application to an abstract Dirac operator is also considered.